Labour market tax policy in the EMU - Karl-Heinz Paqué; Jacques Le Cacheux; Michel Didier (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1998)
Contents: 1. Forum Economique Franco-Allemand - Deutsch-Französisches Wirtschaftspolitisches Forum...1 – 2. EMU and the Labour Market - A Speculative Assessment - Karl-Heinz Paqué...2 – 3. Tax Competition in the European Monetary Union: Present and Prospects - Jacques Le Cacheux...14 – 4. Tax Policy under EMU ( Comments on the Paper Presented by Jacques Le Cacheux) - Michel Didier...31
Keywords: 330